Psychoemotional and Somatic Indicators in Relation to Quality of Life Among Medical Students at Different Stages of Training - Boretska Анастасія; Kleban Катерина (Psychosomatic Medicine and General Practice, 2026)
Background. Psychoemotional disturbances and somatic symptoms are common among medical students and can be accompanied by a decrease in quality of life and impaired adaptation to the educational process. Objective. To analyze the relationship between psychoemotional and somatic manifestations and quality of life among medical students at different stages of training. Materials and methods. The study involved 193 medical students of О.О. Bogomolets National Medical University, from the first to the sixth year of study, aged 18 to 24 years. Data collection was carried out by anonymous online survey using the Google Forms platform. The Generalized Anxiety Disorder 7-item scale (GAD-7), the Beck Depression Inventory-II (BDI-II), the Somatic Symptom Scale-8 (SSS-8), and the quality of life assessment scale (ed. prof. Chaban O.S.) (CQLS) were used to assess the psychoemotional state and somatic manifestations. Statistical processing of the results was carried out using descriptive statistics, the Student’s t-test, and Spearman’s rank correlation coefficient. Results. The level of anxiety in the studied sample ranged from 9.5 ± 4.1 to 11.4 ± 5.0 points, the level of depressive symptoms ranged from 19.5 ± 8.3 to 24.2 ± 9.6 points, somatic symptoms ranged from 13.9 ± 5.9 to 17.6 ± 6.1 points, and quality of life indicators ranged from 50.8 ± 15.8 to 59.5 ± 19.0 points. Statistically significant inter-year differences were found for individual indicators of somatic symptoms, depressive manifestations, anxiety, and quality of life (p < 0.05). Statistically significant direct correlations were found between the level of anxiety, depressive manifestations, and somatic symptoms: GAD-7 ↔ SSS-8 (rₛ = 0.554; p < 0.001), BDI-II ↔ SSS-8 (rₛ = 0.562; p < 0.001), GAD-7 ↔ BDI-II (rₛ = 0.567; p < 0.001). Statistically significant inverse correlations were found between quality of life indicators and the level of anxiety (rₛ = −0.412; p < 0.001), somatic symptoms (rₛ = −0.444; p < 0.001), and depressive manifestations (rₛ = −0.763; p < 0.001). Discussion. The obtained results indicate a close relationship between psychoemotional and somatic manifestations among medical students. Higher levels of anxiety and depressive symptoms were associated with a greater somatic symptom burden and lower quality of life. Depressive symptoms demonstrated the strongest association with quality of life indicators. Conclusions. The obtained results confirm the interconnected nature of psychoemotional and somatic manifestations in medical students. Depressive symptoms demonstrated the strongest association with quality of life. The identified features support the need for early psychodiagnostic screening and the implementation of medical and psychological support programs for medical students. Keywords: medical students, psychoemotional state, anxiety, depressive symptoms, somatic symptoms, quality of life.